2023
DOI: 10.7759/cureus.50547
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Physiotherapy Approach for Autism With Speech Impairment and Attention Deficit: A Case Report

Pradhyum D Kolhe,
H V Sharath,
Vaishnavi M Thakre
et al.

Abstract: Autism is a disorder distinguished by significant challenges in social interaction and communication coupled with repetitive and stereotypical patterns of behavior and activities. Deficits in social interaction and language development become apparent before age three. In children, this condition is referred to as autism spectrum disorder (ASD). Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by persistent patterns of inattention, hyperactivity, and impulsivity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Music therapy [15] The child experiences music that has been altered and adjusted, including different volume levels and pitches.…”
Section: Intervention Procedures Rationalementioning
confidence: 99%
“…Music therapy [15] The child experiences music that has been altered and adjusted, including different volume levels and pitches.…”
Section: Intervention Procedures Rationalementioning
confidence: 99%
“…Several theories speculate that the etiology of DCD is part of the continuum of cerebral palsy is se condary to prenatal, prenatal, or neonatal insult or is secondary to neuronal damage at the cellular level in the neurotransmitter or receptor systems. 11,12 A common concern in the literature is the psychosocial problems showed by DCD children. A number of studies based on observational behavior and standardized questionnaires showed more symptoms of depression and stress/anxiety such as sadness, agitation and panic, low selfesteem in children with DCD compared with their typically developing peers.…”
Section: Introductionmentioning
confidence: 99%